Robust video watermarking algorithm for H.264/AVC based on texture feature - Wei-wei ZHANG; Ru ZHANG; Jian-yi LIU; Xin-xin NIU; Yi-xian YANG (Tongxin xuebao)
On the basis of analyzing some existing video watermarking al ithms and combining with the new features of the H.264/AVC video coding standard,a new robust video watermarking algorithm based on texture feature was proposed.The proposed algorithm firstly performs the 4×4 integer discrete cosine transform on the current frame in purpose of identifying whether it is the texture block.Then the watermarking is embedded by adopting the way of differential energy for selecting the appropriate coefficients adaptively.The experimental result shows that the proposed algorithm has little impact on the video quality and bit-rate,moreover,its robustness can effectively resist the common attacks such as the gauss noise,low pass filter and re-coded performed on the video watermarking.